Therapeutic effect and potential mechanism of Fufang Danshen dripping pills for stable coronary heart disease: a randomized controlled trial - Meng, Li-qin; Huang, Pei-ying; Li, Qing-min; Feng, Yu-chao; Li, Ding-jian; Wu, Guang-long; Ao, Bo-wen; Wu, Guo-chao; Zhang, Guo-xiong; Chen, Bo-jun (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe efficacy and mechanism of Fufang Danshen dripping pills (FFDS) in the secondary prevention of stable coronary heart disease (SCHD) is currently undetermined. This study aims to investigate the efficacy and preliminary mechanism by which FFDS may impact the progression of SCHD.MethodsBased on randomization, we administered oral FFDS to 30 patients with SCHD in addition to conventional treatment for 30 days. After treatment, three-months major adverse cardiovascular events (MACE) were assessed as the primary outcome. Additionally, we evaluated the patients' Seattle Angina Questionnaire score, blood pressure, circulating levels of total cholesterol, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, triglycerides, C-reactive protein, platelets, alanine aminotransferase, aspartate aminotransferase, serum creatinine, and fasting blood glucose as the secondary outcomes. Furthermore, we utilized mass spectrometry analysis, network pharmacology, and lipidomics to predict the potential mechanisms of FFDS in the treatment of SCHD.ResultsFollowing treatment, FFDS demonstrated significant improvements in serum triglyceride levels (P = 0.013) and a reduction in the frequency of angina episodes (P = 0.021). We conducted mass spectrometry analysis on FFDS and identified 236 chemical components. Lipidomics further confirmed triglycerides as key lipids affected by FFDS. By integrating these findings with network pharmacology targets, we highlighted the potential roles of LPL, CD36, FABPpm, L-FABP, LCAT, and CEPT in fat digestion, absorption, and metabolism pathways, suggesting their involvement in FFDS's treatment of SCHD by reducing triglycerides.ConclusionIn individuals with SCHD, the administration of FFDS has been shown to effectively reduce circulating triglyceride levels and decrease the frequency of angina episodes. This therapeutic effect is likely due to the active components of FFDS targeting key proteins: LPL, CD36, FABPpm, L-FABP, LCAT, and CEPT.Clinical Trial Registrationhttps://www.chictr.org.cn/, identifier (ChiCTR2400080149).